Commercial dynamics between Hispania and Mauretania Caesariensis. Some considerations from pottery evidence (Ist-Vth centuries AD) - Alejandro QUEVEDO SÁNCHEZ (Zephyrus, 2019)
During Antiquity the two shores of the western Mediterranean, the Iberian Peninsula and the Maghreb, shared a rich common past favoured by their close geographical proximity. However, our knowledge of the exchanges between the two territories is very uneven. While archaeological research in the “Circle of the Strait” has advanced exponentially in recent decades, data for the eastern sector are still based mainly on epigraphic and literary documentation. This approach, which highlights the value of socio-political links, is insufficient for trade analysis: the information is imprecise and does not allow the volume of transactions carried out to be accurately evaluated. The aim of this paper is to study the nature and intensity of the economic relations between the coasts of Northern Algeria and those of the peninsular east on the basis of pottery evidence. The selection of this material is motivated by its continuity in the archaeological record. In this paper I propose a qualitative and quantitative analysis of the preserved ceramic material, crossing the most recent data with the reinterpretation of old archaeological contexts already published. Chronologically, the study extends from the Roman annexation of Mauretania Caesariensis to Late Antiquity.